UNTERWEGS-‐‑SEIN IN EUROPA ZWISCHEN VERGANGENHEIT UND ZUKUNFT. BENJAMINS UND BOBROWSKIS „WANDERER“ - Maria Behre (Anuari de Filologia: Literatures Contemporànies, 2015)
In his Denkbilder, the Jewish philosopher and homme de lettre Walter Benjamin describes scenes from European metropolises. He offers a glance at quite heterogeneous and freely chosen life styles of the turbulent nineteen-twenties to sketch a possible future for Europe. Today’s reader of the Denkbilder can hardly suppress the memory of a political and personal crisis, namely that of Benjamin’s flight across the Pyrenees, which ended in the Spanish harbour town Portbou. In the poem Der Wanderer, the writer Johannes Bobrowski, a resident of East Berlin, captures the life of a wanderer who depends on the hospitality of others, because he is either persecuted or his freely chosen lifestyle requires him to roam about. For both authors, travelling becomes a substitute for “Heimat” and also a way of life that represents the future of Europe. This forward-looking attitude is based on the experience of cataclysmic events that have been memorably expressed in highly literate apocalyptic images. The writer and graphic designer Christoph Meckel emphasizes how life rises out of ruins only to return to them, by embedding the lyrical process in Eastern European villages, thereby creating a country for which Bobrowski had chosen the mythological name “Sarmatia”, which stands for a messianic utopian vision shared by Benjamin and others.